Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica) - Peña Cantero, Álvaro L.; Marzal, Marina Fresneda (Zootaxa, 2018)
Peña Cantero, Álvaro L., Marzal, Marina Fresneda (2018): Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). Zootaxa 4441 (1): 121-136, DOI:10.11646/zootaxa.4441.1.7